Frontiers in Internet Technologies - Su, J (Springer, 2015)
This book constitutes the refereed proceedings of the Second CCF Internet Conference of China, ICoC 2013, held in Zhangjiajie, China, in July 2013. The 24 revised full papers presented were carefully reviewed and selected from 63 submissions. The papers address issues such as future Internet architecture, Internet routing, network security, network management, data center networks, green networks, wireless networks, P2P networks, mobile Internet and the Internet of Things.